FAM13A affects body fat distribution and adipocyte function - Fathzadeh, Mohsen; Li, Jiehan; Rao, Abhiram; Cook, Naomi; Chennamsetty, Indumathi; Seldin, Marcus; Zhou, Xiang; Sangwung, Panjamaporn; Gloudemans, Michael J.; Keller, Mark; Attie, Allan; Yang, Jing; et al. (Nature communications, 2020)
Genetic variation in the FAM13A (Family with Sequence Similarity 13 Member A) locus has been associated with several glycemic and metabolic traits in genome-wide association studies (GWAS). Here, we demonstrate that in humans, FAM13A alleles are associated with increased FAM13A expression in subcutaneous adipose tissue (SAT) and an insulin resistance-related phenotype (e.g. higher waist-to-hip ratio and fasting insulin levels, but lower body fat). In human adipocyte models, knockdown of FAM13A in preadipocytes accelerates adipocyte differentiation. In mice, Fam13a knockout (KO) have a lower visceral to subcutaneous fat (VAT/SAT) ratio after high-fat diet challenge, in comparison to their wild-type counterparts. Subcutaneous adipocytes in KO mice show a size distribution shift toward an increased number of smaller adipocytes, along with an improved adipogenic potential. Our results indicate that GWAS-associated variants within the FAM13A locus alter adipose FAM13A expression, which in turn, regulates adipocyte differentiation and contribute to changes in body fat distribution. Genetic variants in the FAM13A locus have been associated with anthropometric and glycemic traits. Here, using fine-mapping, in vitro knockdown studies in pre-adipocytes and in vivo knockout in mice, the authors show that FAM13A is involved in regulating fat distribution and metabolic traits.